Risk assessment of atherosclerotic cardiovascular diseases before statin therapy initiation: Knowledge, attitude, and practice of physicians in Yemen - Al-Ashwal, Fahmi Y.; Syed Sulaiman, Syed Azhar; Sheikh Ghadzi, Siti Maisharah; Kubas, Mohammed Abdullah; Halboup, Abdulsalam (Public Library of Science (PLOS), 2022)
Background Risk evaluation of atherosclerotic cardiovascular disease (ASCVD) remains the cornerstone of primary prevention. The cardiovascular risk assessment can guide the decision-making on various preventive measures such as initiating or deferring statin therapy. Thus, our study aimed to assess the physicians knowledge, attitude, and practices regarding atherosclerotic cardiovascular diseases risk assessment. Also, we evaluated the physician-patient discussion and counseling practices before statin therapy initiation in concordance with recommendations from the latest clinical practice guideline. Methods A cross-sectional study was conducted between November 2020 and January 2021. A self-administered questionnaire was distributed to 350 physicians (GPs, residents, specialists, and consultants). Two trained pharmacists distributed the questionnaires in 5 major tertiary governmental hospitals and more than ten private hospitals. Also, private clinics were targeted so that we get a representative sample of physicians at different workplaces. Results A total of 270 physicians filled the questionnaire out of 350 physicians approached, with 14 being excluded due to high missing data, giving a final response rate of 73%. Participants had suboptimal knowledge and practices with a high positive attitude toward atherosclerotic cardiovascular diseases risk assessment. The knowledge and practices were higher among consultants, participants from the cardiology department, those with experience years of more than nine years, and those who reported following a specific guideline for cholesterol management or using a risk calculator in their practice. Notably, the risk assessment and counseling practices were lower among physicians who reported seeing more patients per day. Conclusion Physicians had overall low knowledge, suboptimal practices, and a high positive attitude toward cardiovascular risk assessment. Therefore, physicians training and continuing medical education regarding cholesterol management and primary prevention clinical practice guidelines are recommended. Also, the importance of adherence to clinical practice guidelines and their impact on clinical outcomes should be emphasized.